The Improvement of Students' Ability to Learn Cell Biology and Discuss its Application in Live Through the Implementation of the Student Team Achievement Divisions (STAD) with Lesson Study (LS) - Marheny Lukitasari; Herawati Susilo (Bandar Lampung University (UBL), 2014)
The purpose of the research is to improve students' ability to learn Cell Biology and discuss its application in live through the implementation of the Student Team Achievement Divisions (STAD) with Lesson Study (LS) in lecture. The experiment was conducted by applying the LS activities involving six lecturers and eleven final year students who are members of the LS team for fourteen meetings on Biology Cell lectures. There are seven Cell Biology materials that were implemented in two different classes with the use of STAD models. The Lesson Study that include Plan, Do, and See activities was implemented with the purpose of improving the quality of teaching learning processes. The data of learning ability was measured using quiz at the end of each lecture, while the discussion ability data was obtained through observation of the 2nd, 3rd, 4th, 5th, and 7th using the observation sheet with aspects of observations: a) the contribution to the task, b) leadership, c) collaboration, d) ability to cooperate, e) understanding of the materials, f) presentation style, and g) the quality of the questions raised. Descriptive data were analyzed qualitatively for the observed components. The highest results of the average of quiz of seven Cell Biology materials was the result of learning on the Nucleus and Genetics Materials. On the average the highest quiz result on this seventh meeting for class A was 67.93 and for class B was 64.21. The discussion abilities of the five materials discussed during Cell Biology lectures was during the discussion of the Structure and Function of the Cytoskeleton. On the average the discussion abilities on this fifth discussion for class A was 68.08 and for class B was 73.50.